Ozonation in direct filtration - (:unkn) unknown (TAYLOR & FRANCIS INC, 2002)
The effects of pre-ozonation on the effluent quality and the head losses through a deep filter were investigated using two identical deep bed filters receiving the same raw water. One of the influents to the filters was pre-ozonated and the other was aerated using identical contact chambers and diffusers. It was observed that the pre-ozonated filter resulted in significantly better effluent quality. It was found that the delay time after the pre-ozonation process has an important effect in direct filtration. The shorter the delay time, the less is the head loss and the better is the effluent quality. Indices that calculate Specific Energy (cm of head required per grain of solids captured) in deep bed filters were developed. The Filterability Index given in the literature and the Specific Energy values were used to compare the performance of the two identical filters receiving the same raw water. It was shown that the pre-ozonated water required on average 1.1 times more specific energy compared to the same aerated water and the experiments with short ozone delay times had on average 4.9 times less specific energy compared to the long delay experiments.
Keywords: ozone; ozonation; direct filtration; deep bed filters; particle counting; filterability index; INDUCED PARTICLE DESTABILIZATION